Multifunctional metamorphic III-V distributed Bragg reflectors grown on Si substrate for resonant cavity surface emitting devices - Tsimafei Laryn; Rafael Jumar Chu; Yeonhwa Kim; Eunkyo Ju; Chunghyun Ahn; Hyun-Yong Yu; May Madarang; Hojoong Jung; Won Jun Choi; Daehwan Jung (PhotoniX)
Abstract Surface-emitting optoelectronic devices such as vertical cavity surface emitting lasers are important for various applications. However, the devices are typically grown on expensive and small-size III-V substrates. Si substrates can offer much improved scalability, lower cost and higher thermal properties but present significant challenges such as the formation of crystalline defects from the heteroepitaxial growth of III-V semiconductors on Si. Here, we propose multifunctional metamorphic In0.1Ga0.9As/AlAs distributed Bragg reflectors (DBRs) on Si which serve as a bottom mirror with a high reflectivity of 99.8% while simultaneously reducing the crystalline defect density by a factor of three, compared to GaAs/AlAs DBR on Si. The proposed DBR structure also exhibits a crack-free and exceptionally smooth surface morphology with root-mean-square roughness of 1.2 nm, which is five times smoother than the conventional GaAs/AlAs structure on Si. Furthermore, as proof of concept, InAs quantum dot surface-emitting diodes are fabricated on the metamorphic III-V DBR/Si templates and their performances are analyzed in comparison to those grown on native GaAs wafers. A narrow electroluminescence linewidth of 11.5 meV is observed, confirming that the multifunctional metamorphic DBR is promising for a scalable and more techno-economic surface-emitting III-V optoelectronics grown on Si substrates.